A crash course in forces and motion with Max Axiom, super scientist - Sohn, Emily, author; Barnet, Charles, illustrator; Erwin, Steve, illustrator (London : Raintree, 2008)
Graphic science demonstrates and explains science. Whether shrinking down to the size of an ant or riding on a sound wave, it makes science a lot more accessible, by explaining science concepts and reinforcing scientific knowledge.